Diagnostic accuracy of pleural fluid adenosine deaminase in tubercular pleural effusion - Aniruddha Udupa K; S. Vinod Kumar; Manju R; H. Nandeesha (International Journal of Medical Research and Review, 2016)
Background: In India, tuberculosis is an endemic disease. Delay in diagnosis results in poor prognosis and fast spread of the disease. The objective of the present study is to look for an effective and acceptable diagnostic test, which may be helpful to initiate early treatment to improve prognosis and reduce spread. The presence of ADA in pleural fluids reflects the cellular immune response in the pleural cavity and in particularly, the activation of T lymphocytes. Objective of study include evaluating efficacy of combined use of ADA activity diagnosing tuberculous pleural effusion.Methods: Biochemistry, cytology, and microbiology studies were performed on 164 consecutive pleural fluids. ADA were determined on all exudative effusions.Results: Pleural fluid ADA activity at a level of ≥40 U/L, the sensitivity=95.5%, specificity=93.4%, positive prediction value=94.4%, negative prediction value=94.7% and efficacy= 94.5 %. It was statistically significant (p value<0.001).Conclusion: ADA is a highly sensitive diagnostic marker of tubercular pleural effusion.